RESEARCH PROGRESS ON MAJOR DISEASES OF PIGS AND YAKS ON THE QINGHAI-TIBET PLATEAU: A COMPREHENSIVE REVIEW FROM 1990 TO 2023 - Hui Zhang; Peipei Tian; Mujeeb Ur Rehman; Fareeda Kebzai; Ying Li (Journal of Animal and Plant Sciences, 2024)
The increased prevalence of diseases in Tibetan pigs and yaks has significantly hampered the cultivation industry, leading to substantial socioeconomic losses and adversely affecting both Tibetan pig production and the livelihoods of surrounding nomads. To conduct a comprehensive analysis, relevant articles on epidemics affecting Tibetan pigs and yaks from 1990 to 2023 were collected from five databases: CNKI, Google, PubMed, Science Direct, and Web of Science. The study findings, covering the period 1990 to 2023, revealed that Tibetan pigs faced primarily challenges from the porcine epidemic diarrhea virus (PEDV), Swine flu, Cysticercus tenuicollis, diarrheagenic Escherichia coli (DEC) and Enterococci. Zoonotic diseases such as Trichinosis, Swine flu, Hepatitis E virus (HEV), Toxoplasma gondii, Cystic echinococcosis (CE), and Japanese encephalitis virus were prevalent in the Tibetan pig area. Meanwhile, the yaks experienced severe outbreaks caused by bovine coronavirus (BCoV), bovine rotavirus A (BRVA), Echinococcus granulosus, Neosporosis IgM, Theileria spp. and Anaplasma spp., significantly impacting their quality of life. Primary risk factors for diseases in Tibetan pigs and yaks included age, housing conditions, frequency of deworming and vaccinations, and environmental factors on the plateaus. This review aims to improve regional breeding practices for Tibetan pigs and yaks by addressing these risk factors, thus reducing the prevalence of various diseases in the future. Achieving these objectives will not only elevate the local socioeconomic status, but also establish the Tibetan pig and yak industry as an independent and flourishing sector.
Keywords: Tibetan pigs; Yaks; Epidemics; Zoonotic diseases; Risk factors